1988
DOI: 10.1016/s0886-3350(88)80012-9
|View full text |Cite
|
Sign up to set email alerts
|

Specular microscopy of the anterior lens capsule after endocapsular lens implantation

Abstract: Endocapsular phacoemulsification and complete in-the-bag intraocular lens (IOL) fixation was performed on 77 eyes. Specular microscopy of the anterior lens capsule was performed postoperatively, and the process of anterior capsule opacification after endocapsular cataract surgery was classified. Lens epithelial cells on the inner surface of the anterior lens capsule, facing the optical portion of the IOL, underwent a diffuse fibrosis. In more peripheral areas, where the anterior and posterior capsules were tig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In rabbit eyes, in which extensive postoperative capsular opacification usually occurs, the Ering prohibited PCO without preoperative and postoperative local or general medication. 6 In electron microscopic 14,16,37 and immunohistochemical observations, including the in situ hybridization technique, the postoperative changes under the anterior capsule and equator were the same as during normal wound healing. 38 Fagerholm et al 39 reported the same concept earlier.…”
Section: Commentmentioning
confidence: 84%
See 2 more Smart Citations
“…In rabbit eyes, in which extensive postoperative capsular opacification usually occurs, the Ering prohibited PCO without preoperative and postoperative local or general medication. 6 In electron microscopic 14,16,37 and immunohistochemical observations, including the in situ hybridization technique, the postoperative changes under the anterior capsule and equator were the same as during normal wound healing. 38 Fagerholm et al 39 reported the same concept earlier.…”
Section: Commentmentioning
confidence: 84%
“…4,14 Because Kleinmann et al 15 reported that the capsular bag can survive anatomically without the LECs, this seems to be a rational approach, but all trials failed. During actual clinical surgery, it is almost impossible to remove all LECs superiorly, and if any LECs remain, they transform into fibroblastlike cells, 16 anterior capsular opacification occurs, and the subsequent PCO cannot be prevented. In addition, there is no chemical procedure to remove all LECs completely and safely.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using a slitlamp and a conventional specular microscope, in vivo LECs have only been observed on the surface of an intraocular lens and near the rim of the anterior capsular opening after cataract surgery [12][13][14]. The specular images of LECs in the crystalline lens in vivo were not well visualized when they were compared with those of corneal endothelial cells [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%